Development of a Virtual Lab in Science-Physics Learning Based on the STEM Approach - Mulia Rahmi; Saminan Saminan; Muhammad Syukri; Yusrizal Yusrizal; Ibnu Khaldun; Wiwit Artika; Ismul Huda (Postgraduate, University of Mataram, 2022)
Learning innovation in the laboratory has experienced very rapid development in the current era of technological development. One of these innovations is through the use of virtual laboratory classes in science learning, as is the case with temperature and heat materials. The aims of this research are to develop a virtual lab based on the STEM approach on the concepts of temperature and heat, to test the validity and practicality of virtual lab products based on the STEM approach. The development method used is 4-D (four-D). The data obtained in the form of quantitative and qualitative data. Qualitative data in the form of suggestions, input, feedback and criticism from the validator and quantitative data in the form of a validation questionnaire. The validation results show that the validation is 87.89% (very feasible). In addition, the practical test of student responses was obtained at 96, 15 (very practical) and the teacher at 3.31 (very practical). Practically speaking, the virtual lab based on the STEM approach that was developed is very useful to support practical activities.